Preparation of polyurethane foams from Hydroxytelechelic oligoisoprenes obtained by controlled degradation of natural rubber : study of their physico-mechanical, thermal, and acoustic properties - Anuwat Saetung (2011)
Thesis (Ph.D., Polymer Technology)--Prince of Songkla University, 2009